Comparison of Dream Analysis from the Perspective of Ibn Qutaibah and Calvin S Hall - Abd. Hamid Cholili; Hilda Halida; Abu Amar Nashih Bilqisth; Nurin Amalia Hamid (Jurnal Penelitian Medan Agama, 2026)
This study examines the discourse on dream psychology by comparing the perspectives of Islamic and modern psychology, drawing on the work of Ibn Qutaibah and Calvin S. Hall. This study is motivated by the paradigm differences between the Islamic tradition, which views dreams as symbolic-spiritual phenomena, and modern psychology, which positions dreams as reflections of individual cognitive processes and psychological experiences. Although the study of dreams has been widely discussed in both scholarly traditions, comparative research specifically comparing the thoughts of Ibn Qutaibah and Calvin S. Hall is still relatively limited. Therefore, this study makes a novel contribution to efforts to establish an integrative dialogue between Islamic scholarship and modern psychology in understanding the phenomenon of dreams. This study uses a qualitative approach with a literature review and comparative analysis. Primary sources include Ibn Qutaibah's Ta'wil al-Ru'ya and Calvin S. Hall's A Cognitive Theory of Dreams, supported by classical Islamic literature and contemporary psychological studies on dreams. The results indicate that Ibn Qutaibah interpreted dreams through a symbolic, spiritual, and transcendental approach, grounded in divine messages and individual moral development. In contrast, Hall views dreams as manifestations of an individual's cognitive processes, life experiences, emotions, and psychological dynamics. Despite fundamental epistemological differences, both perspectives view dreams as meaningful phenomena that reflect humankind's inner state. This research contributes to enriching the development of Islamic and modern psychology through a more holistic approach to dream analysis within the context of contemporary psychology.